The Efficiency of Sukuk Indices by Different Tenures Following the 2008-Financial Crisis - Rahim, Syazwani Abd (Current Aspects in Business, Economics and Finance Vol. 2, 2022)
The sukuk market in the Islamic capital market has evolved and grown significantly. During the 2008 global financial crisis, the deteriorating economic conditions of countries, particularly Malaysia, the world's largest sukuk market, had a negative impact on the value of sukuk investments. The 33% decrease in total global sukuk issuance following the 2008 crisis created a complicated situation among sukuk investors (who classified sukuk as a risky investment), which increased the number of sukuk defaults. In addition, the high volatility has an impact on long-term efficiency. The Dow Jones Sukuk 1-3 Year Total Return Index (DJSUK3TR) and Dow Jones Sukuk 7-10 Year Total Return Index (DJSUK7TR) provide daily data for all sukuk indices (DJSUK10TR). As a result, using the GARCH-in-Mean (GARCH-M) model, this study investigates the types of sukuk market efficiency before, during, and after the 2008 global financial crisis. The Efficient Markets Hypothesis (EMH) and the Random Walk model are used in the analyses. The results show that the long-term sukuk index (DJSUK10TR) provides the best market performance analysis. Overall, the sukuk market is considered inefficient. In short, the findings will provide valuable information and guidelines and give issuers, policymakers, regulatory bodies, and investors confidence to invest in and issue sukuk. The empirical contributions in this study demonstrate the significance of sukuk in encouraging investors to invest in sukuk to boost economic growth and investment.